Analysis of electrical parameters of organic thin film transistors based on thickness variation in semi‐conducting and dielectric layers. Issue 2 (1st March 2014) - Kumar, Brijesh; Kaushik, Brajesh Kumar; Negi, Yuvraj Singh
Abstract : This research study analyses the impact of semi‐conductor ( t osc ) and dielectric ( t ox ) thicknesses on top contact (TC) and bottom contact (BC) organic thin film transistors (OTFTs) using Atlas 2‐D numerical device simulation. Thickness of each layer is varied from 20 to 150 nm. The parameters such as electric field, charge carrier distribution and trap density are analysed from device physics point of view with variations in organic semi‐conductor layer and dielectric thicknesses. A decrease of 22% in TC to BC current ratio is observed for maximum increase in t osc, whereas, it remains almost constant at unity with variations in t ox . Furthermore, the maximum mobility for TC is achieved at t osc of 20 nm and reduces monotonically with further increase in thickness because of lowering of average charge. However, its highest value is obtained at 60 nm for BC structure that declines with positive or negative change in t osc . Besides this, the threshold voltage ( V t ) shows a reduction of 50% for both the structures on scaling down t ox from 150 to 20 nm. Furthermore, the ON to OFF current ratio is found to be more dependent on t osc as compared with t ox . This is because of a dominant impact of t osc reduction on OFF current as compared with impact of t ox reduction on the ON current. Additionally, a decrease in contact resistance ( R C ) is observed in TC structure for thicker active layer while operating at lower Vgs . However, at high gate voltage, t osc maps to the access resistance that results in higher R C values.